Peran Zakat Produktif dalam Meningkatkan Pemberdayaan Ekonomi Mustahik di Kota Blitar Berbasis KUA - Nurjihan Khasanah; Tsani Nurnailaz Zulfa; Lusi Rahma Dayanti; Aninda Lailya (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2026)
This study examines the role of productive zakat in enhancing mustahiq economic empowerment through the Umat Economic Empowerment Program (PEU) based on KUA institutional collaboration. The research is grounded in the need to optimize zakat distribution beyond consumptive assistance toward sustainable economic strengthening. A qualitative descriptive case study approach was employed, utilizing in-depth interviews, field observations, documentation, and a survey of selected mustahiq beneficiaries. The findings indicate that productive zakat contributes positively to business continuity, entrepreneurial motivation, and early signs of economic independence. The revolving capital scheme and mentorship mechanisms play a significant role in fostering financial discipline and productive behavior. However, limitations remain in business management capacity, particularly in financial administration. The study implies that productive zakat effectiveness depends on the integration of financial support, capacity building, and institutional synergy. Strengthening managerial training and sustained assistance is essential to ensure long-term empowerment outcomes.